Seismic control of tall buildings using vertically distributed multiple tuned mass dampers - Akhlagh Pasand, Ali; Zahrai, Seyed Mehdi (The structural design of tall and special buildings, 2024)
Summary Tuned mass damper (TMD) is a seismic vibration control device used to reduce wind and seismic vibrations of structures. Although TMD is attractive to many researchers due to its simplicity, optimizing its parameters and positions is very challenging. The sensitivity of TMD to structure's frequency changes is among its weaknesses and if parameters of this system are not optimally tuned, the efficiency of this system decreases. To solve this problem, multiple tuned mass dampers (MTMDs) have been proposed. In this research, in order to study and compare single tuned mass damper (STMD) with MTMDs vertically distributed according to modal analysis, a 20‐story building is used. The structure is analyzed in OpenSees under seven ground motions with a peak ground acceleration (PGA) of 1.0 g. To optimize TMD parameters, particle swarm optimization (PSO) algorithm is used and the results are compared to those obtained from Den Hartog's approach. To be able to use PSO algorithm and optimize TMD design parameters, Matlab and OpenSees are linked together. In this paper, more than one vibration mode is used to tune and distribute dampers to overcome higher mode effects in high‐rise buildings. The results showed that depending on their different layouts and different optimization methods used, MTMDs reduce the average maximum responses of the structure by up to 12.1%. This is while STMD is able to reduce maximum responses of the structure by 4.3%.